2008
DOI: 10.1002/jqs.1209
|View full text |Cite
|
Sign up to set email alerts
|

Glacial dynamics in southernmost South America during Marine Isotope Stage 5e to the Younger Dryas chron: a brief review with a focus on cosmogenic nuclide measurements

Abstract: The timing of major glacial changes between Marine Isotope Stage (MIS) 5e and the Younger Dryas chron (YD) in southern South America is reviewed. Focus is placed on studies that use cosmogenic nuclide measurements. However, other dated records and modelling results are also discussed to provide the broader glacial geological context. Limits on the state of glacial geologic knowledge are examined and suggestions are made as to how some of these can be addressed in future studies. Studies show that on the east s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 81 publications
3
27
0
1
Order By: Relevance
“…Mercer, 1968, 1976, 1982, 1983. Subsequent efforts to develop the glacial history of the PIS have used a wide range of geochronological techniques and are well summarised by several review papers on Quaternary (McCulloch et al, 2000;Rabassa and Clapperton, 1990;Rabassa and Coronato, 2009;Kaplan et al, 2008a;Glasser et al, 2004;Rodbell et al, 2009;Clapperton, 1993;Harrison and Glasser, 2011;Rabassa et al, 2000) and pre-Quaternary (Rabassa et al, 2011) glaciations.…”
Section: (B) Estimated Extent Of the Pis At The Lgm Showing Sites Menmentioning
confidence: 99%
“…Mercer, 1968, 1976, 1982, 1983. Subsequent efforts to develop the glacial history of the PIS have used a wide range of geochronological techniques and are well summarised by several review papers on Quaternary (McCulloch et al, 2000;Rabassa and Clapperton, 1990;Rabassa and Coronato, 2009;Kaplan et al, 2008a;Glasser et al, 2004;Rodbell et al, 2009;Clapperton, 1993;Harrison and Glasser, 2011;Rabassa et al, 2000) and pre-Quaternary (Rabassa et al, 2011) glaciations.…”
Section: (B) Estimated Extent Of the Pis At The Lgm Showing Sites Menmentioning
confidence: 99%
“…The mountain glacier chronologies for southern South America, around 458 S, are reviewed by Kaplan et al (2008). They show that glacial chronologies varied across the southern Andes.…”
Section: South Americamentioning
confidence: 99%
“…A recent synthesis and analysis of the Late Quaternary glacial geochronology of Patagonia by Kaplan et al (2008a) concluded that glacial events during Marine Isotope Stage 2 (MIS2) were broadly in-phase with other areas around the globe. This analysis also revealed some differences in glacial histories along N-S and W-E transects at millennial timescales during T1, which could result from genuine spatial and temporal climate variability or geologic uncertainties (geomorphological, stratigraphic and dating methods).…”
Section: Introductionmentioning
confidence: 99%